Comparative Life Cycle Assessment of Lithium-ion Battery Recycling Methods - Järvenpää, Maiju (My University, 2025)
Lithium-ion batteries (LIBs) are a critical part of the modern-day energy storage, but their environmental risks are urgent threats that need to be recognized. One main concern associated with LIBs are the rare materials and scarce natural resources that they contain. Recovering these scarce materials is the main goal of LIB recycling. Because of these environmental threats, life cycle assessment (LCA) has become more important for assessing the environmental impacts associated with LIBs, and their recycling. This thesis first introduces LIBs; their structure, environmental concerns and three recycling methods; pyrometallurgy, hydrometallurgy and direct recycling. LIBs are complex structures used in various fields from consumer electronics to electric vehicles. Given the growing demand of these batteries, their recycling necessity is doubtless. The three main recycling methods for LIBs are pyrometallurgy, hydrometallurgy and direct recycling, each with their own advantages. The basic framework, aim, types and standards of LCA are explained by the thesis. Understanding LCA methodology is crucial for identifying the environmental impacts of a process. Finally, the results gather the information of three LCA studies, one for each recycling method and discusses the difference of each LCA and recycling method in terms of environmental impact and system boundaries. Recognizing the differences in the system boundaries between the LCA studies is important for a successful comparison. The emphasis is finding the most environmentally friendly recycling method by comparing LCAs. This thesis underlines the significance of identifying the environmental impacts associated with LIB recycling methods for achieving sustainability.

Litiumioniakut ovat kriittinen osa nykypäivän energiataloutta, mutta niiden ympäristöriskit ovat ajankohtaisia ongelmia, jotka ovat tärkeä tunnistaa. Litiumioniakkujen ensisijainen huolenaihe on niiden sisältämät harvinaiset materiaalit ja niukat luonnonvarat. Näiden niukkojen materiaalien talteenotto on litiumioniakkujen kierrätyksen päätavoite. Ympäristöuhkien vuoksi elinkaarianalyysi on noussut yhä tärkeämmäksi työkaluksi litiumioniakkujen ja niiden kierrätyksen ympäristövaikutusten tunnistamiseksi. Tämä tutkielma esittelee ensin litiumioniakut; niiden rakenteen, ympäristön huolenaiheet ja kolme kierrätysmenetelmää: pyrometallurgian, hydrometallurgian ja suoran kierrätyksen. Litiumioniakut ovat monimutkaisia rakenteita, joita käytetään eri aloille kuluttajien elektroniikasta sähköajoneuvoihin. Näiden akkujen kasvava kysyntä nostaa esille niiden kierrätystarpeen. Litiumioniakkujen kolme ensisijaista kierrätystapaa ovat pyrometallurgia, hydrometallurgia ja suora kierrätys, joista jokaisella on omat etunsa. LCA:n vaiheet, tavoite, toimintatavat ja standardit selitetään tutkielmassa. LCA:n toiminnan ymmärtäminen on ratkaisevan tärkeää prosessien ympäristövaikutusten tunnistamisessa. Lopuksi tulokset kokoavat kolme LCA-tutkimusta ja käsittelee kunkin LCA:n ja kierrätysmenetelmän erot ympäristövaikutusten ja järjestelmärajojen osalta. Onnistuneen vertailun kannalta LCA-tutkimusten erilaiset järjestelmärajat ovat tärkeä tunnistaa. Näin ympäristöystävällisimmän kierrätysmenetelmän litiumioniakuille voi löytää LCA:ta hyödyntämällä. Tämä tutkielma korostaa litiumioniakkujen kierrätykseen liittyvien ympäristövaikutusten tunnistamisen tärkeyttä kestävän kehityksen saavuttamiseksi.
Keywords: Life cycle assessment, lithium-ion battery, sustainability, recycling, environmental impacts, energy storage, elinkaarianalyysi, litiumioniakku, kestävyys, kierrätys, ympäristövaikutukset, energian varastointi